Cervical and intracranial artery dissections [Servi̇kal ve i̇ntrakrani̇al arter di̇seksi̇yonlari] - (:unkn) unknown (Turkish Society of Cerebrovascular Diseases, 2012)
Spontaneous Cervical Artery Dissections (CADs) constitute 25% of young and middle age ischemic strokes. It is most frequently seen between the ages of 45±10. Annual incidence was reported as 2-3/100.000 for internal carotid artery and half of it for vertebral artery. Suspicion and awareness for diagnosis positively affect the treatment and prognosis. The reasons of dissection may trauma, connective tissue diseases, migraine, hypertension and smoking. As a result of subintimal dissection, lumen may become narrow and haemodynamic infarctions may occur. Thrombosis occurred on the vessel wall can cause infarctions. Subarachnoid haemorrhage may emerge result from pseudoaneurysm. Clinical findings may include focal neurological signs such as head and neck pain, tinnitus, Horner Syndrome and lower cranial nerve involvement, but acute ischemic stroke may be observed in about two thirds of cases. Two types of aneurysm can occur; saccular and fusiform. A good prognosis has been observed for aneurysms due to the cervical artery dissection in long-time follow-up studies; cerebral ischemia, local compression and rupture are not seen and 36% of them will disappear over time. Subarachnoid haemorrhage risk is higher in intracranial artery dissections as a result of subadventitial dissection. Recurrence rate is about 1% in different series. Because of CADISS (Cervical Artery Dissection in Stroke Study) Study still continues, anticoagulation is now more preferable compared to antiagregants for medical treatment. Thrombolytic treatment has been applied in small series, but randomised controlled studies are needed.
Keywords: Aneurysm; Cervical artery dissection (CAD); Medical treatment